Model Strategi Pembelajaran Berbasis Spiritual dalam Kitab Ta’lim al-Muta’allim - Fadhilah Sukmawati Tanjung; Udin Supriadi; Mokh. Iman Firmansyah; Muhammad Hizba Aulia (Halaqa: Journal of Islamic Education, 2025)
Meaningful education demands active engagement between teachers and students through appropriate learning strategies. An effective learning process should consider the spiritual dimension as a core element in developing human potential. This study aims to explore spiritual-based learning strategies as presented in Ta’lim al-Muta’allim, a classical Islamic educational text by Shaykh al-Zarnuji. This research employs a qualitative approach using the library research method. Spiritual intelligence is viewed as an inner capacity to find meaning and values in life, connecting the individual to metaphysical reality and the Divine. The results reveal that the spiritual-based learning strategies found in the text include: (1) designing learning based on students’ real needs; (2) presenting materials in accordance with students’ level of understanding, supported by media such as inspirational videos and religious-social activities; (3) creating enjoyable and age-appropriate classroom environments through arts, play, or storytelling; and (4) assigning reflective tasks such as reading, writing, and internalizing lessons to enhance students’ understanding and application of the materials in daily life. The novelty of this study lies in the integration of spiritual values into classical pedagogical strategies, offering practical implications for strengthening students’ character and spiritual awareness in the context of contemporary Islamic education.